Studies on the properties of pervious fly ash–cement concrete as a pavement material. Issue 1 (1st January 2017) - Muthaiyan, Uma Maguesvari; Thirumalai, Sundararajan
Abstract: The aim of this study is to investigate the effect of variation of cement content, partial replacement of cement by 10 and 20% of fly ash, partial replacement of coarse aggregate by fine aggregates (ranging from 5 to 15%) with the addition of plasticizer on the characteristics of pervious concrete. Class C fly ash was used for the production of pervious concrete, adopting ACI method of mix proportioning. Coarse aggregates of size 19 to 9.5 mm and 9.5 to 4.75 mm blended in the ratio of 60:40 respectively, a constant water—binder ratio of 0.3, a plasticizer of 0.8% by weight of cement were adopted. Density, compressive strength, flexural strength, split tensile strength, total voids, permeable voids, permeability by falling head method, sand blasting abrasion and cantabro abrasion were determined. Replacement of cement by fly ash (up to 20%) has reduced the compressive strength marginally, whereas, addition of fine aggregates (5–15%) has increased the above strength ranging from "marginal" to "high". Incorporation of fly ash has the effect of reduction in total voids in fly ash–cement pervious concretes. It is seen that reduction in total void reduces the sand blasting abrasion and cantabro loss in pervious cement concrete and fly ash cement concrete. All the mixes considered in this study with minimum cement content 250 kg/m 3 and with 10 and 20% of replacement of cement by fly ash with fines content 10 and 15% can be considered for the application of DLC as a base coarse for rigid/flexible pavements.